Embryonic temperature has long-term effects on muscle circRNA expression and somatic growth in Nile tilapia - Rbbani, Golam; Murshed, Riaz; Siriyappagouder, Prabhugouda; Sharko, Fedor; Nedoluzhko, Artem; Joshi, Rajesh; Galindo-Villegas, Jorge; Raeymaekers, Joost A. M.; Fernandes, Jorge M. O. (Frontiers in Cell and Developmental Biology, 2024)
Embryonic temperature has a lasting impact on muscle phenotype in vertebrates, involving complex molecular mechanisms that encompass both protein-coding and non-coding genes.Circular RNAs (circRNAs) are a class of regulatory RNAs that play important roles in various biological processes, but the effect of variable thermal conditions on the circRNA transcriptome and its long-term impact on muscle growth plasticity remains largely unexplored. To fill this fish knowledge gap, we performed a transcriptomic analysis of circRNAs in fast muscle of Nile tilapia (Oreochromis niloticus) subjected to different embryonic temperatures (24, 28 and 32 °C) and then reared at a common temperature (28 °C) for four months. Nile tilapia embryos exhibited faster development and subsequently higher longterm growth at 32°C compared to those reared at 28°C and 24°C. Next-generation sequencing data revealed a total of 5141 unique circRNAs across all temperature groups, of which 1604, 1531, and 1169 circRNAs were exclusively found in the 24 °C, 28 °C and 32 °C groups, respectively. Among them, circNxen exhibited a 1.7-fold (log 2 ) up-regulation in the 24 °C group and a 1.3-fold (log 2 ) up-regulation in the 32 °C group when compared to the 28 °C group.Conversely, circTTN and circTTN_b were down-regulated in the 24 °C groups compared to their 28 °C and 32 °C counterparts. Furthermore, these differentially expressed circRNAs were found to have multiple interactions with myomiRs, highlighting their potential as promising candidates for further investigation in the context of muscle growth plasticity. Taken together, our findings provide new insights into the molecular mechanisms that may underlie muscle growth plasticity in response to thermal variation in fish, with important implications in the context of climate change, fisheries and aquaculture.